University Social Responsibility: An Analysis from the Carrollâ€™s Model - Bastos, Fernando Clemente Cunha; de Souza, Maria José Barbosa; Hoffmann, Estela Maria (Revista de Negócios, 2019)
The university social responsibility contributes to neutralize the factors that lead to social, economic and cultural inequalities and to achieve the development. Aiming to analyze the stakeholders’ perception about the University Social Responsibility (USR) actions, according the Carroll’s Model, an exploratory and descriptive research was performed at two Universities in South Brazil. Semi-structured interviews and documents analysis were part of the qualitative stage. On the other hand, a survey with 1,117 answers was part of the quantitative stage. The results revealed the universities fully meet all the model dimensions. However, during the interviews it was possible to notice there are matters that need to be improved according the USR principles, in both universities. The quantitative research results revealed that the stakeholders’ perception shows significant differences, especially when it comes about the ethical and economic dimensions. As a theoretical contribution, this research provided the use of an academic model of CSR applied to Brazilian universities context. As an empirical contribution, the research provided enough information to improve the universities social responsibility management, plus to the addition of institutional programs.